Fear of Falling in Older Adults: Comprehensive Review - Dukyoo Jung, PhD, RN (Elsevier, 2008)
Fear of falling has been reported in a high percentage of community-dwelling elderly who both do and don't have a history of falling. The aims of this review are to: (a) elucidate the definition of fear of falling; (b) clarify measurements of fear of falling based on its definition; and (c) describe the risk factors for fear of falling. Despite the importance of the percentage and the consequences of fear of falling, its definition is still vague and warrants clarification. Based on a literature review, major fear of falling measurements involve the evaluation of fear of falling and use of a fall efficacy scale. Using a correct definition of fear of falling, nurses working close with older adults need to identify the different definitions of fear of falling and fall efficacy scale. In addition, nurses who work closely with older adults should encourage them to increase or maintain modifiable factors by maximizing their basic health status and enhancing their physical activity to decrease fear of falling.